SUBSURFACE DRAINAGE IMPACTS ON CROPPING INTENSITY IN PAKISTAN - A. H. Azhar; M. M. Alam; M. Latif (Journal of Animal and Plant Sciences, 2011)
Four subsurface tile drainage projects namely; Mardan SCARP Project (MSP), Fourth Drainage Project, Faisalabad (FDP), Chashma Command Area Development Project (CCADP) and Mirpurkhas Tile Drainage Project (MKDP) have been assessed in terms of their impacts on improvement of cropping intensity. The investigations revealed that total cropping intensities (CI) have been improved ranging from 19% (MKDP) to 67% (CCADP) as compared to the pre-project conditions. At MSP, the target value of CI (180%) was not only achieved but also showed an extra upward trend up to 230%. Similarly, at CCADP an upward trend of 162% was observed against the target value of 150%. The four study sites in terms of percent improvement in total CI in the order from maximum to minimum were ranked as: CCADP (67%) > FDP (54%) >MSP (40%) >MKDP (19%), indicating how various project sites were benefited from the drainage activity in those areas. The main reasons for slow benefits at study sites were the limited financial resources available with farmers to reclaim/restore the fertility of waste lands, and shortage of irrigation supplies during the post-construction period to leach down the excess salts. This aspect revealed that efforts put to alleviate the problems of waterlogging & salinity through implementation of tile (pipe) drainage systems had not been up to the expectations mainly due to other associated problems. However, the overall quantitative comparison did indicate the positive impact of tile drainage systems in terms of improving the CI at all study sites.
Keywords: subsurface drainage; impact; crop intensity; waterlogging; salinity; irrigation